Teacher Performance and Classroom Environment on Student Attitude Toward Indonesian Language Learning - Sri Sukasih (Yayasan Keluarga Guru Mandiri, 2022)
This study investigates the impact of the relationship between teacher performance and classroom environment on student attitudes toward Indonesian language learning. This study was carried out using an ex post facto quantitative approach at a primary school in Semarang Regency, Indonesia. The sample of this research consisted of 172 students enrolled by random sampling technique. Data were collected using questionnaires. The data analysis techniques used were descriptive analysis and regression analysis. The Results indicate that teacher performance had a significant influence on student attitudes toward Indonesian language learning, and the classroom environment had a significant influence on student attitudes toward the Indonesian language. Teacher performance and classroom environment may be substantial factors in student attitudes toward Indonesian language learning.